Analyzing Context Clues in Novel Based on Bauman's Theoretical Framework - Laily, Almadani Durotul (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
Context clues are valuable tools employed by authors to assist readers in comprehending unfamiliar or complex vocabulary. These clues, whether intentionally or inadvertently provided, facilitate the reader's understanding and interpretation of the word in question. Drawing upon Bauman's theoretical framework, the present study sought to investigate the diverse contextual cues utilized by the author within the literary work entitled